2009
DOI: 10.1111/j.1744-7402.2009.02419.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Nucleation and Growth Rates, Time-Temperature Transformation Diagram, and Mechanical Properties of a SiO2-Al2O3-CaO-MgO-(R2O) Glass in the Presence of Cr2O3, Fe2O3, and TiO2 Nucleants

Abstract: The crystallization of a SiO2–Al2O3–CaO–MgO–(R2O) glass in the presence of Cr2O3, Fe2O3, and TiO2 nucleants was investigated utilizing differential thermal analyses, X‐ray diffraction, and scanning electron microscope. The optimum nucleation and growth rates of aluminian diopside crystals was determined for the most promising glass specimen containing all three nucleants as 1018 m3/s and 6.17 ± 0.55 × 10−9 m/s, respectively. A time–temperature transformation (TTT) diagram was also constructed for 82 wt% crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Previous studies on the effect of TiO 2 as a nucleating agent in similar glass compositions suggest that additions around 5‐10 wt% (3.6‐7.2 mol%; Table ) will likely not aid crystallization of CMAS. Indeed, in the current study, significant crystallization was not detected until about 12.5‐15 wt% TiO 2 was added to the glass.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the effect of TiO 2 as a nucleating agent in similar glass compositions suggest that additions around 5‐10 wt% (3.6‐7.2 mol%; Table ) will likely not aid crystallization of CMAS. Indeed, in the current study, significant crystallization was not detected until about 12.5‐15 wt% TiO 2 was added to the glass.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of CPGC developed here, nucleating agents were added as per Table , using lower quantities, but keeping the same ratios (1:1:0.6) as was suggested by Rezvani and co-workers . The DSC curves for this glass displayed a sharp exothermic peak at 850 °C which was largely independent of the particle size, as shown in Figure (top three curves), indicative of bulk crystallization.…”
Section: Introductionmentioning
confidence: 94%
“…Rezvani et al suggested that bulk nucleation can occur synergistically when a combination of Cr 2 O 3 , Fe 2 O 3 , and TiO 2 are used, with 5, 5, and 3 wt % respectively, reported as optimal. 31 During nucleation, it is believed that Cr 3+ precipitates from the glass matrix and interacts with Mg 2+ and Fe 2+ ions, forming the (Mg)(Fe,Cr) 2 O 4 spinel, with these spinel acting as nuclei for the final precipitation of diopside crystals through epitaxial growth.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To facilitate the crystallization, effective nucleation agents are normally added to reduce the crystallization activation energy through heterogeneous nucleation on the proper nuclei, such as P 2 O 5 , TiO 2, ZrO 2 , CaF 2 , and Cr 2 O 3. Ma and Hsiang considered that addition of TiO 2 and ZrO 2 into the CAMS‐based glass‐ceramics led to phase separation during annealing process, because Ti 4+ and Zr 4+ are ions with high electric field strength. As a result, small droplets with different chemical composition precipitated in the glass matrix.…”
Section: Introductionmentioning
confidence: 99%